PASANG RI KAJANG: THE NOBLE VALUES OF KAJANG TRADITIONAL COMMUNITY IN BULUKUMBA REGENCY - Raodah, Raodah (Kementerian Pendidikan dan Kebudayaan, 2021)
This study aimed to describe the noble values of Pasang in the beliefs of Kajang traditional community in South Sulawesi. Pasang ri Kajang is an oral message containing guidance, customary rules, guidelines, and institutionalized norms by Turie Arakna (God Almighty) to the first Ammatoa (the first people) for the all members of Kajang traditiobal community. These oral messages inherited from generation to generation, from the first Ammatoa into the present Ammatoa according to the faith teachings of Patuntung. Ammatoa as a traditional leader is mandated to carry out all the rules containing in Pasang, supervised the teaching violations of Pasang, and practiced the all teachings of Pasang as cultural values growth in Kajang traditional community. The glory of a person depended on his/her obedience to Pasang called Tu Salama (saved people). The people who throughout their lives adhere to the values of Pasang will feel an enjoy life. The essence of Pasang is to surrender to Turie Arakna, which means surrender to the God willing, do all teachings and avoid all prohibitions of Pasang. This study used descriptive qualitative method. Data collection techniques were interview, observation, and literature study, then be analyzed inductively. From the result study, it is known that there were three noble values of Pasang ri Kajang, namely the relationship between humans with their God, humans with humans, and human with nature. The relationship between humans with their God as the embodiment of values of Pasang ri Kajang is the essence of Manuntungi truth based on the Patuntung belief by Kajang traditional community.